1990
DOI: 10.1111/j.1574-6968.1990.tb04883.x
|View full text |Cite
|
Sign up to set email alerts
|

Exocellular polysaccharides produced by lactic acid bacteria

Abstract: The production of homopolysaccharides (dextrans, mutans) and heteropolysaccharides by lactic acid bacteria, their chemical composition, their structure and their synthesis are outlined. Mutans streptococci, which include Streptococcus mutans and S. sobrinus produce soluble and insoluble α‐glucans. The latter may contain as much as 90%α‐1–3 linkages and possess a marked ability to promote adherence to the smooth tooth surface causing dental plaque. Dextrans produced by Leuconostoc mesenteroides are high molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
239
1
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(260 citation statements)
references
References 79 publications
9
239
1
11
Order By: Relevance
“…The highest exopolysaccharide producing isolate strain was L. plantarum (810.75 mg/L) whereas, the least exopolysaccharide producing isolate was L. crispatus (242.5 mg/L). The values obtained for EPS production and cell dry weight were comparable with data obtained in previous experiments with lactic acid bacteria species/strains (Cerning, 1990; Cerning, Bouillanne, Landon, & Desmazeaud, 1992; Korakli et al., 2003; Minervini et al., 2010; Mozzi, Savoy de Giori, Oliver, & Font de Valdez, 1996; Vogel, 2008). Other studies have also reported that some microorganisms are capable of producing and excreting over 40 g/L of EPSs under conditions of stress (Lin & Cheng‐Chien, 2007; Papinutti, 2010; Ravella et al., 2010).…”
Section: Resultssupporting
confidence: 88%
“…The highest exopolysaccharide producing isolate strain was L. plantarum (810.75 mg/L) whereas, the least exopolysaccharide producing isolate was L. crispatus (242.5 mg/L). The values obtained for EPS production and cell dry weight were comparable with data obtained in previous experiments with lactic acid bacteria species/strains (Cerning, 1990; Cerning, Bouillanne, Landon, & Desmazeaud, 1992; Korakli et al., 2003; Minervini et al., 2010; Mozzi, Savoy de Giori, Oliver, & Font de Valdez, 1996; Vogel, 2008). Other studies have also reported that some microorganisms are capable of producing and excreting over 40 g/L of EPSs under conditions of stress (Lin & Cheng‐Chien, 2007; Papinutti, 2010; Ravella et al., 2010).…”
Section: Resultssupporting
confidence: 88%
“…EPS produced by lactic acid bacteria have apparent molecular masses that range from 1´10 4 to >1´10 6 g·mol -1 [4]. Therefore the low value obtained could be ascribed to the lost of a fraction of low molecular weight (lower than 12 000) in the dialysis water.…”
Section: Discussionmentioning
confidence: 95%
“…Dairy LAB are weak EPS producers. EPS production in milk depends strongly on the fermenting species even at strain level and ranges in concentration between 25 and 890 mg·L -1 [4]. Optimisation of the growth environment (temperature, pH, carbon and nitrogen sources) is important to achieve maximal EPS production.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Based on their composition, EPS from LAB can be subdivided into two groups, namely homopolysaccharides (HoPS) and heteropolysaccharides (HePS). HoPS are composed of one type of constituting monosaccharides (D-glucopyranose or D-fructofuranose) and can be produced in amounts of up to 40 g L −1 from sucrose by the action of glycosyltransferases.…”
Section: Introductionmentioning
confidence: 99%